2002
DOI: 10.1007/s00134-002-1268-8
|View full text |Cite
|
Sign up to set email alerts
|

Decision to extubate

Abstract: The need for reintubation within 24-72 h of planned extubation is a common event, occurring in 2-25% of extubated patients. Risk factors for extubation failure include being a medical, multidisciplinary or paediatric patient; age >70 years; a longer duration of mechanical ventilation; use of continuous intravenous sedation; and anaemia (haemoglobin <10 g/dl or haematocrit <30%) at the time of extubation. The pathophysiology of extubation failure can be distinct from that seen with weaning failure and includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
164
4
35

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(220 citation statements)
references
References 121 publications
(72 reference statements)
4
164
4
35
Order By: Relevance
“…This finding supports the results of a previous study that demonstrated that children who remain longer on IMV and that have a lower SpO 2 generally are associated with failure of weaning [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding supports the results of a previous study that demonstrated that children who remain longer on IMV and that have a lower SpO 2 generally are associated with failure of weaning [20].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, there is a failure rate of 15% of children who are unsuccessfully weaned [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…MODS was defined as the incidence of more than two organ dysfunctions. We followed the guidelines specified for neuromuscular blockade and sedative agents (22), lung protective ventilation (23,24), and spontaneous breathing trials (25).…”
Section: Data Collectionmentioning
confidence: 99%
“…This condition occurs in 2 to 25% of extubated patients (1)(2)(3). Extubation failure increases the incidence of mortality, pneumonia, number of days in the intensive care unit (ICU) and hospital, time spent on mechanical ventilation (MV), hospital costs, and the need for a tracheostomy (4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated an increased incidence of reintuba-tion, pneumonia, and prolonged MV among such patients (2)(3)(4)(5)7,9,14,15).…”
Section: Introductionmentioning
confidence: 99%